РЕЦЕПЦИЈАТА НА ХОМЕРСКАТА ПОЕЗИЈА ВО НАЈСТАРИ ВРЕМИЊА (Philological Studies, 2019)
This article points the differences between ancient and modern forms of reception of Homer’s poetry. Special attention is given to the questions about where this tradition occurs and develops and how this poetry spread across the ancient world. In that context, this article pays attention to the literary evidences of the presence of Homer’s poetry into the Macedonian cultural environment from the ancient period (Aristotle, Zoilus, Joannes Stobaeus). This evidence unequivocally refers to the processes of communication with written texts as part of educational processes, as well as critical observations of the Homer’s poetry in ancient times.
Keywords: Homer, epic poetry, literary reception, antiquity, Macedonian cultural environment